2023
DOI: 10.1002/ps.7387
|View full text |Cite
|
Sign up to set email alerts
|

Californian thistle (Cirsium arvense): endophytes and Puccinia punctiformis

Abstract: Californian thistle (Cirisum arvense) is a troublesome weed in pastures and cropping systems. The fungal biocontrol agent Puccinia punctiformis, commonly referred to as thistle rust, performs inconsistently on C. arvense. Problems with P. punctiformis establishment and control of C. arvense may be attributable to differing plant endophytic populations in various environments. This article provides an overview of the relationships between endophytes and their host, but also between endophytes and pathogens with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 82 publications
(253 reference statements)
0
5
0
Order By: Relevance
“…For example, microbial symbionts of insects provide essential functions and coevolve with their hosts, and can facilitate invasions by providing detoxification capabilities and/or aiding host range expansion ( Lange et al 2023 ). Similarly, the absence or presence of plant endophytes can determine if a plant becomes invasive ( Kentjens et al 2023 ), and rapid adaptation and dispersal have led to spatial variation in the resistance of the cane toad ( Rhinella marina ) to its native-range lungworm parasite ( Rhabdias pseudosphaerocephala ) ( Eyck et al 2022 ).…”
Section: Identifying Future Threatsmentioning
confidence: 99%
“…For example, microbial symbionts of insects provide essential functions and coevolve with their hosts, and can facilitate invasions by providing detoxification capabilities and/or aiding host range expansion ( Lange et al 2023 ). Similarly, the absence or presence of plant endophytes can determine if a plant becomes invasive ( Kentjens et al 2023 ), and rapid adaptation and dispersal have led to spatial variation in the resistance of the cane toad ( Rhinella marina ) to its native-range lungworm parasite ( Rhabdias pseudosphaerocephala ) ( Eyck et al 2022 ).…”
Section: Identifying Future Threatsmentioning
confidence: 99%
“…The meeting was organized into twenty‐two 50‐min presentations with ample time for discussion. Sixteen of the articles in this issue are from conference participants 2–17 . Four related articles from non‐participants are also included 18–21 .…”
Section: Figurementioning
confidence: 99%
“…Puccinia punctiformis (F. Strauss) Rohl. (thistle rust) is a heterotrophic fungal pathogen of C. arvense that acts as a longterm systemic parasite (Buller, 1950;Menzies, 1953;Berner et al, 2013;Kentjens et al, 2023). As a parasite that consumes resources and weakens the root structure (Buller, 1950;Menzies, 1953), P. punctiformis is specific to C. arvense (Berner et al, 2013;Kentjens et al, 2023) and has been identified in temperate habitats around the globe (Berner et al, 2013;Kentjens et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…(thistle rust) is a heterotrophic fungal pathogen of C. arvense that acts as a longterm systemic parasite (Buller, 1950;Menzies, 1953;Berner et al, 2013;Kentjens et al, 2023). As a parasite that consumes resources and weakens the root structure (Buller, 1950;Menzies, 1953), P. punctiformis is specific to C. arvense (Berner et al, 2013;Kentjens et al, 2023) and has been identified in temperate habitats around the globe (Berner et al, 2013;Kentjens et al, 2023). Once established in the roots, infected C. arvense can develop chlorotic leaf tissue with lesions, elongated stems, and growth irregularities which can reduce fitness and cause death (Buller, 1950;Berner et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation